2011
DOI: 10.1111/j.1529-8817.2011.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Mastophoroideae (Corallinales, Rhodophyta) and Polyphyly in Nongeniculate Species Widely Distributed on Pacific Coral Reefs1

Abstract: The subfamily Mastophoroideae (Corallinaceae, Rhodophyta) is characterized by species possessing nongeniculate, uniporate tetrasporangial conceptacles without apical plugs, the presence of cell fusions, and the absence of secondary pit connections. However, molecular phylogenetic studies not including the type genus Mastophora indicated that the Mastophoroideae was polyphyletic. Our molecular phylogenetic analysis of the subfamily including the type genus using DNA sequences of SSU rDNA and plastid-encoded gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
154
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(165 citation statements)
references
References 47 publications
(122 reference statements)
11
154
0
Order By: Relevance
“…This evolutionary trajectory is supported both by the fossil record (Aguirre et al, 2010;Kundal, 2011) and by molecular phylogenetics (Bailey and Chapman, 1998;Bittner et al, 2011;Kato et al, 2011). Moreover, these data suggest that articulated thalli are polyphyletic, evolving from crustose corallines multiple times and leading to three distinct phylogenetic groups of articulated coralline algae: Corallinoideae, Amphiroideae and Metagoniolithoideae ( Fig.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…This evolutionary trajectory is supported both by the fossil record (Aguirre et al, 2010;Kundal, 2011) and by molecular phylogenetics (Bailey and Chapman, 1998;Bittner et al, 2011;Kato et al, 2011). Moreover, these data suggest that articulated thalli are polyphyletic, evolving from crustose corallines multiple times and leading to three distinct phylogenetic groups of articulated coralline algae: Corallinoideae, Amphiroideae and Metagoniolithoideae ( Fig.…”
Section: Introductionmentioning
confidence: 50%
“…Mechanical Kato et al, 2011). 'Amphiroideae' refers to Amphiroideae sensu Johansen (1981), and is separated from the rest of Lithophylloideae here for clarity.…”
Section: Materials and Methods Specimen Collectionmentioning
confidence: 99%
“…However, Kato et al (2011) concluded that differences in trichocyte arrangement could be used to separate the two supported lineages at a generic level: Hydrolithon for horizontally arranged fields of trichocytes with interspersed vegetative filaments, and Porolithon (resurrected) for horizontally arranged, tightly packed fields of trichocytes without interspersed vegetative filaments. Similarities in the formation of cells around the pores of tetrasporangial conceptacles led the latter authors to propose that Porolithon is a heterotypic synonym of Hydrolithon.…”
Section: Discussionmentioning
confidence: 99%
“…Bailey et al (2004) used molecular biology techniques, but not morphological features, and combined P. pachydermum with Hydrolithon pachydermum (Foslie 1904: 4) Bailey, Gabel & Freshwater (2004: 8), as did Broom et al (2008), who recognised genetic similarities between H. pachydermum and H. onkodes. Kato et al (2011) used molecular analyses of SSU rDNA and psbA sequences to divide Japanese coralline algae into independent polyphyletic lineages for the Mastophoroideae genera examined (Hydrolithon, Neogoniolithon, Pneophyllum Kützing (1843: 385), Porolithon and Spongites). They also proposed the establishment of three new subfamilies, Hydrolithoideae (including Hydrolithon), Porolithoideae (including the resurrected genus Porolithon) and Neogoniolithoideae (including Neogoniolithon).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation